POLA PEMELIHARAN TERNAK BABI (Sus sucrofa) OLEH ORANG ASLI PAPUA DI DISTRIK KAMU KABUPATEN DOGIYAI - Nurlaila Susilawati Palenga; Herianto Toding (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2022)
Dogiyai Regency is one of the regencies in Papua Province. One of the livelihoods of the Indigenous Papuan people in Kamu District, Dogiyai Regency is raising pigs. Raising pigs by the Papuan Indigenous People community is a source of livelihood other than farming, and is the main source of income. The business potential of pig farmers in Kamu District, Dogiyai Regency has good prospects for development, because it is the livelihood of the Papuan Indigenous people in Kamu District, Dogiyai Regency, apart from farming. This study aims to determine the pattern of raising pigs (Sus sucrofa) by indigenous Papuans in Kamu District, Dogiyai Regency. This research was carried out in Kamu District, Dogiyai Regency for 1 (one) month, starting from April 01 to May 01, 2022. The method used in this study was a descriptive method with interview and observation techniques, using a questionnaire tool or a list of questions with research variables to be observed or studied The results showed that pigs had been raised by Papuan natives for a long time, so that the respondent farmers could be said to have experience in raising pigs. The management pattern for maintaining and health of pigs by Indigenous Papuan people in Kamu District, Dogiyai Regency, is mostly still traditional, but a small number have been rearing their pigs in a semi-traditional or semi-intensive way. The pattern of reproductive management of pigs by Indigenous Papuan people in Kamu District, Dogiyai Regency, most of them generally already know and apply reproductive management, although there are still a few who have not implemented reproductive management.